Impact assessment of sustainable endoparasite control for small ruminants - Derige-Montes, Nimfa; Zapata, Normito R. Jr. (2010)
Parasites bring tremendous economic losses to local goat production. The Philippines actively pursues a technology development strategy intended to effectively control parasites. In 2001 to 2003, a Technical Assistance Grant 443 (TAG 443) project entitled "Development and Testing of an Integrated Approach to the Control of Gastro-intestinal Parasites in Small Ruminants in South East Asia" was implemented in the Philippines, Indonesia and Vietnam to reduce morbidity and mortality in goat production and, thus, improve farm productivity. This project involved a "participatory" technology development process where stakeholders actively generated and adopted parasite control technologies in a sustained manner.
The impact assessment study analyzes and evaluates the various socioeconomic impacts of selected technologies developed through the Sustainable Endoparasite Control (SPC) for Small Ruminant Project (ACIAR 97133) and TAG 443. The farmer-generated baskets of technologies revolved around strategic deworming control and also included strategies for all aspects of goat production management such as housing and confinement, nutrition and feeding, breeding, disease control, grazing, and sanitation. These technologies were developed and tested by farmers according to their needs, resources, and capabilities. An offshoot of TAG 443, the Farmer Livestock School was developed by the Philippine Council for Agriculture, Forestry and Natural Resources Research and Development, in collaboration with the Livestock Division of the Department Agriculture, local farmers to adopt these technologies.
Using the Australian Center for International Agricultural Research's framework of mapping inputs to benefits, the study found that farmers have realized initial concrete benefits from such participatory development process. These include: 1) decreased morbidity and mortality; 2) increased stocks; 3) positive financial impacts based on benefit-cost analysis; 4) increased personal competence of farmers and extension workers; and 5) improved social competence.
Keywords: Ruminants -- Feeding and feeds